Sosialisasi Kebijakan StimulusPerekonomian Nasional kepada UMKM terdampak Covid-19 untuk Mengurangi Resiko Kredit Macet - Moh Wahyudin Zarkasyi; Rahmi Zubaedah; Indah Laily Hilmi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this research is to reduce the risk of bad credit, help MSME business actors, so that it is easy to access information and find problems related to decreased income and monitoring carried out by most MSME players during the Covid-19 pandemic. The method of implementing thematic KKN is done by using and creating social media. This social media facility is used to search for data, socialize, and provide counseling to MSME partners including making applications, Whatsapp groups, Instagram, Facebook, Twitter, Youtube. The results showed that UMKM Partners understand the existence of a national economic policy stimulus for MSMEs affected by Covid-19 and some of them have received micro-business assistance from the government. The conclusion of this research is that there are still UMKM partners who do not respond to the economic stimulus provided by the government, MSME business actors affected by Covid-19, socialization of the economic stimulus policy and assistance to MSMEs with the Whatsapp group to exchange information to improve the business of MSMEs by take advantage of the national policy stimulus provided by the government for MSME business actors.